2005
DOI: 10.1002/agr.20056
|View full text |Cite
|
Sign up to set email alerts
|

An empirical evaluation of factors determining vertical integration in U.S. food manufacturing industries

Abstract: Vertical integration has become an important business strategy among food manufacturers because it allows them to manage and customize their production according to consumer needs. Economic theory has shown that vertical integration may be induced by transaction costs, demand variability, market power motives, and other factors. This paper presents an index of forward vertical integration for U.S. food manufacturing industries and uses an econometric analysis to examine the factors that motivate vertical integ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 21 publications
4
16
0
1
Order By: Relevance
“…The price is controlled by distributors who may not spend time promoting the product value' (M3), 'Modern farmers must understand marketing to deal with various distributors' (M4), and '20% of our products are sold in farmers' markets, 30% by distributors, and the rest in our own store' (M6). This result, like those of previous studies (Bhuyan, 2005;De Moura et al, 2009), indicated that marketing has become an essential skill for modern farmers, helping them promote product value, manage interactions with distributors, and increase revenue.…”
Section: Social Networksupporting
confidence: 70%
See 2 more Smart Citations
“…The price is controlled by distributors who may not spend time promoting the product value' (M3), 'Modern farmers must understand marketing to deal with various distributors' (M4), and '20% of our products are sold in farmers' markets, 30% by distributors, and the rest in our own store' (M6). This result, like those of previous studies (Bhuyan, 2005;De Moura et al, 2009), indicated that marketing has become an essential skill for modern farmers, helping them promote product value, manage interactions with distributors, and increase revenue.…”
Section: Social Networksupporting
confidence: 70%
“…Fourth, the recent literature on agribusiness strategy (e.g., Bhuyan, 2005;De Moura et al, 2009) has stressed that social networks are a strategic resource. The results of this study demonstrated that specific types of supply chains (i.e., technology vendors and knowledgeable experts) and strategic alliances (both horizontal and vertical) benefit Taiwanese agribusiness.…”
Section: External Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence to support the hypothesis that vertical integration increases as concentration in the supplier market increases, even controlling for asset specificity, has been obtained in various prior studies (e.g., Levy 1985;Caves, Bradburd 1988;Leiblein et al 2002). In terms of food industries, Frank and Henderson (1992) and Bhuyan (2005) find supporting evidence for vertical integration in the U.S. food manufacturing industries. The small-numbers bargaining hypothesis is therefore as follows:…”
Section: H1supporting
confidence: 55%
“…This is because internalization comes at the cost of additional bureaucracy and weaker incentives (Williamson 1985). Empirical evidence has been provided to support this idea (Martin 1986;Scherer, Ross 1990;Russo 1992;Bhuyan 2005). All of this leads us to consider the following hypothesis:…”
Section: H4mentioning
confidence: 99%